Custodiol-N™ cardioplegia lowers cerebral inflammation and activation of hypoxia-inducible factor-1α. (18th January 2019) - Hoyer, Alexandro; Then Bergh, Florian; Klaeske, Kristin; Lehmann, Sven; Misfeld, Martin; Borger, Michael; Dieterlen, Maja-Theresa
Abstract: OBJECTIVES: Cardioplegic solutions induce cardiac arrest and protect cardiac tissue from ischaemia-reperfusion injury. However, the effects on the brain, which is vulnerable to cardiopulmonary bypass (CPB) surgery and ischaemia-reperfusion injury, mostly remain unknown. We investigated if cardioplegic solutions differ in their effects in altered oxygen conditions and in their ability to induce cerebral inflammation. METHODS: Thirty pigs were subjected to a midline sternotomy and CPB at 34°C with 90 min cardiac arrest followed by 120 min reperfusion. Following randomization on a 1:1:1 basis, they received either a single shot of histidine-tryptophan-α-ketoglutarate (HTK)-Bretschneider solution ( n  = 10), histidine-tryptophan-α-ketoglutarate-N (HTK-N; n  = 10) or HTK plus 1.2 mg/l cyclosporine A (HTK/CsA; n  = 10). Brain regions of interest (frontal cortex, cerebellum, brain stem, diencephalon, colliculus superior) were analysed by real time quantitative reverse transcriptase polymerase chain reaction for hypoxia-inducible factor-1α (HIF-1α), tumour necrosis factor-α, interleukin (IL)-10, IL-1β and IL-1β receptor as well as by immunohistochemical analysis for HIF-1α. Blood gas and electrolyte analyses were performed. RESULTS: Comparisons between baseline and reperfusion period levels revealed that HTK-N cardioplegia induced a smaller reduction of the haemoglobin content and blood calcium concentrations (hbbaseline : 5.97 ± 0.63 mmol/l; hbreperfusion : 6.16 ± 0.66 mmol/l; P  = 0.428; Ca baseline 2 + : 1.36 ± 0.05 mmol/l; Ca reperfusion 2 + : 1.28 ± 0.05 mmol/l; P  < 0.001) compared to HTK (hbbaseline : 5.93 ± 0.45 mmol/l; hbreperfusion : 4.72 ± 0.79 mmol/l; P  = 0.001; Ca baseline 2 + : 1.34 ± 0.07 mmol/l; Ca reperfusion 2 + : 1.24 ± 0.06 mmol/l; P  = 0.004) and HTK/CsA cardioplegia (hbbaseline : 5.88 ± 0.44 mmol/l; hbreperfusion : 5.14 ± 0.87 mmol/l; P  = 0.040; Ca baseline 2 + : 1.38 ± 0.04 mmol/l; Ca reperfusion 2 + : 1.20 ± 0.14 mmol/l; P  = 0.001). Brain region-specific regulation of the HIF-1α expression, no general HIF-1α activation and a lower tumour necrosis factor-α expression (pto HTK  = 0.050, pto HTK/CsA  = 0.013) were documented for HTK-N cardioplegia. CONCLUSIONS: HTK-N (Custodiol-N) induced fewer cerebral effects and less inflammation during CPB surgery than HTK and HTK/CsA cardioplegia. These data suggest that HTK-N exerts brain protective effects during and after CPB surgery.